Hormone Replacement Therapy Associated White Blood Cell DNA Methylation and Gene Expression are Associated With Within-Pair Differences of Body Adiposity and Bone Mass. (18th December 2015) - Bahl, Aileen; Pöllänen, Eija; Ismail, Khadeeja; Sipilä, Sarianna; Mikkola, Tuija M.; Berglund, Eva; Lindqvist, Carl Mårten; Syvänen, Ann-Christine; Rantanen, Taina; Kaprio, Jaakko; Kovanen, Vuokko; Ollikainen, Miina
Abstract : The loss of estrogen during menopause causes changes in the female body, with wide-ranging effects on health. Estrogen-containing hormone replacement therapy (HRT) leads to a relief of typical menopausal symptoms, benefits bone and muscle health, and is associated with tissue-specific gene expression profiles. As gene expression is controlled by epigenetic factors (including DNA methylation), many of which are environmentally sensitive, it is plausible that at least part of the HRT-associated gene expression is due to changes in DNA methylation profile. We investigated genome-wide DNA methylation and gene expression patterns of white blood cells (WBCs) and their associations with body composition, including muscle and bone measures of monozygotic (MZ) female twin pairs discordant for HRT. We identified 7, 855 nominally significant differentially methylated regions (DMRs) associated with 4, 044 genes. Of the genes with DMRs, five ( ACBA1, CCL5, FASLG, PPP2R2B, and UHRF1 ) were also differentially expressed. All have been previously associated with HRT or estrogenic regulation, but not with HRT-associated DNA methylation. All five genes were associated with bone mineral content (BMC), and ABCA1, FASLG, and UHRF1 were also associated with body adiposity. Our study is the first to show that HRT associates with genome-wide DNA methylation alterations in WBCs. Moreover, we show that five differentially expressed genes with DMRs associate with clinical measures, including body fat percentage, lean body mass, bone mass, and blood lipids. Our results indicate that at least part of the known beneficial HRT effects on body composition and bone mass may be regulated by DNA methylation associated alterations in gene expression in circulating WBCs.